Mapping the Discourse. Architecture Periodicals in/for the Teaching of Architecture History - Gaia Caramellino; Valeria Casali; Nicole De Togni (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The article reflects on the role of architectural journals as sources, instruments, methods and narrative devices for the teaching of architectural history, questioning their role of mediators with a multifaced network of milieux characterized by divergent positions, ideological agendas, and modes of interacting. Moving from the teaching seminar offered over the past six years to internationals students at Politecnico di Milano in the framework of the History and Theory course, the pedagogical project intersects the growing attention for the relations between architecture and media, and the current debate on the history of architecture as a transnational practice.A corpus of around fifty periodicals published in eighteen different countries was addressed as a “system of knowledge” and a “global printed network”, overcoming monographic and local-centered readings based on the history of isolated journals or linked to national editorial cultures and narratives. Journals were examined in their interrelations and interconnections through comparative and cross-cultural analyses, crossing diverse architectural geographies, to trace the international circulation of knowledge.Crossing two divergent research attitudes codified by architectural historians, who tended to look at magazines as structuring sources for writing history or, alternatively, as objects of inquiry over the past decades, journals are critically examined as complex objects, investigated in their economic, material, cultural, visual, and graphic dimensions. By dissecting the overall structure of each journal and scrutinizing their constituting elements - including undervalued parts, often considered at the peripheries of the discourse -, the multi-layered study of this printed network brings to the light the interconnections between a constellation of actors and agents involved in the production of knowledge. The analysis of the diverse agendas, rationalities, editorial strategies and networks between editors, owners, institutions, and the general audience allowed to question the very notion of milieu that the magazines contribute to create. On the one hand, the cross-reading of “journal biographies” and the study of the “anatomy” of diverse genres of magazines contribute to question canonical interpretations and timeframes of a 20th century architectural history still centered on the European and North American editorial scene, offering a more nuanced understanding of the times and forms of production of architectural culture. On the other hand, using a corpus of visual and less-conventional analytical tools and communicative forms revealed the potential of maps, timelines, and diagrams as promising and innovative narrative devices. These means could enrich the corpus of methods and instruments used in the pedagogy of architectural history, opening the discussion on the opportunities offered by innovative forms of contamination with procedures and tools of quantitative research and the technologies and methodologies of the digital humanities.